Raja Haji Fisabilillah : Hannibal dari Riau - Junus, Hasan (Pekanbaru : Yayasan Pusaka Riau, 2000)
Biography of Raja Haji Fisabilillah, an author from Riau Sultanate, Indonesia.
Includes bibliographical references (p. 81-84).
Keywords: Raja Haji Ahmad -- Raja of Riau, -- 1725-1784 -- Biography; Malays -- History; Malay Archipelago -- History